2022
DOI: 10.3389/fmicb.2022.822197
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying Bacterial Uranium Resistance

Abstract: Environmental uranium pollution due to industries producing naturally occurring radioactive material or nuclear accidents and releases is a global concern. Uranium is hazardous for ecosystems as well as for humans when accumulated through the food chain, through contaminated groundwater and potable water sources, or through inhalation. In particular, uranium pollution pressures microbial communities, which are essential for healthy ecosystems. In turn, microorganisms can influence the mobility and toxicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 147 publications
(204 reference statements)
0
3
0
Order By: Relevance
“…Other cytochromes have been found to be imperative to induce uranium reduction in Geobacter as well as in other bacteria such as S. oneidensis . In addition to the periplasmic c7-type cytochrome PpcA, an important intermediate electron carrier (in the absence of hydrogen), GscA ( Geobacter sub-surface c-type cytochrome A), MacA (diheme c-type cytochrome peroxidase), MtrC (also known as OmcB; outer membrane c-type cytochrome) and OmcZ (outer-surface c-type cytochrome) has shown to be essential for the reduction of uranium ( Yun et al, 2016 ; Rogiers et al, 2022 ). Bacterial pili also seem to play a role as an electron conductor between the cells and the electron acceptors.…”
Section: Interaction Mechanisms Between Microorganisms and Relevant R...mentioning
confidence: 99%
“…Other cytochromes have been found to be imperative to induce uranium reduction in Geobacter as well as in other bacteria such as S. oneidensis . In addition to the periplasmic c7-type cytochrome PpcA, an important intermediate electron carrier (in the absence of hydrogen), GscA ( Geobacter sub-surface c-type cytochrome A), MacA (diheme c-type cytochrome peroxidase), MtrC (also known as OmcB; outer membrane c-type cytochrome) and OmcZ (outer-surface c-type cytochrome) has shown to be essential for the reduction of uranium ( Yun et al, 2016 ; Rogiers et al, 2022 ). Bacterial pili also seem to play a role as an electron conductor between the cells and the electron acceptors.…”
Section: Interaction Mechanisms Between Microorganisms and Relevant R...mentioning
confidence: 99%
“…Compared with physical and chemical remediation, bioremediation has the advantages of economy and no secondary pollution, and is widely used in the treatment of environmental pollution (Adams et al, 2015). Microorganisms are key organisms in many elemental cycles on Earth, such as carbon, nitrogen, and sulfur cycles, and strongly influence the transport of various heavy metals (Wegner et al, 2019;Bell et al, 2020;Rogiers et al, 2022). Understanding the interaction between microorganisms and pollutants will provide insights into the mechanism of environmental factors affecting microbial degradation and corresponding biogeochemical processes (Cho et al, 2012;Varjani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that microorganisms can influence uranium mobility through biomineralization with phosphates and carbonates, oxidationreduction reactions, biosorption or uptake and intracellular accumulation (Cologgi et al, 2011;Llorens et al, 2012;Yun et al, 2016;Rogiers, 2022;Yu et al, 2022). However, the underlying molecular mechanisms that entail uranium resistance are largely unknown (Rogiers et al, 2022b). It has been shown that various uranium detoxification mechanisms exist and a single strain can harbor multiple systems (Theodorakopoulos et al, 2015;Yu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%